HIL testing of wheel slide protection systems: criteria for continuous updating and validation - L. Pugi; G. Paolieri; M. Giorgetti; L. Berzi; R. Viviani; L. Cabrucci; L. Bocciolini (Railway Engineering Science, 2023)
Abstract Assessment of railway wheel slide protection (WSP) systems involves the execution of complex experimental activities that are quite expensive and time-consuming, since they involve the physical reproduction of degraded adhesion conditions on a real railway line. WSP is devoted to regulating applied braking forces to avoid excessive wheel sliding in case of degraded adhesion conditions between wheel and rail. WSP must be also compliant to safety specifications related to assured braking performances and consumed air. Hardware in the loop (HIL) testing offers an affordable and sustainable way to accelerate these activities optimizing cost, duration and safety of experimental activities performed online. HIL test rigs are subjected to continuous updates, customization and natural ageing of their components. This work investigates the criteria that can be adopted to assure a continuous monitoring and validation of a real WSP test rig, the Italian test rig of Firenze Osmannoro.